Duchowny jako świadek w procesie o stwierdzenie nieważności małżeństwa - Dappa, Rafał (Ius Matrimoniale, 2015)
The central part of cases to declare the nullity of marriage is investigation. Code of Canon Law enumerates following evidence: the declarations of the parties, proof through documents, witnesses and testimonies, experts, judicial examination and inspection, presumptions. Among these the most popular in cases to declare the nullity of marriage are undoubtedly witnesses and testimonies. It is true that can. 1549 CIC prescribe very wide the possibilities of using these means, however not everyone might be a witness. Among few categories of people unable to witnessing at court, the law enumerates inter alia, priests. However this inability is not absolute and it results from the specific character of pastoral ministry. Main interest of present compilation is an analysis of can. 1548 CIC and can. 1550 CIC according to cleric persons. An inability to witnessing at court resulting from the secrecy of confession, and exemption from obligatory testimonies resulting from conducting sacred ministry, are two basic categories limiting the possibility of calling a clergyman in testimony. The present compilation comprises an attempt of analysis of practical usage of these legal norms.